Preparation and study of the structural and optical properties of Bi2S3 thin films by Spray pyrolysis method (Baghdad Science Journal, 2017)
In this research Bi2S3 thin films have been prepared on glass substrates using chemical spray pyrolysis method at substrate temperature (300oC) and molarity (0.015) mol.Structural and optical properties of the thin films above have been studied; XRD analysis demonstrated that the Bi2S3 films are polycrystalline with (031) orientation and with Orthorhombic structure. The optical properties were studied using the spectral of the absorbance and transmission of films in wavelength ranging (300-1100) nm. The study showed that the films have high transmission within the range of the visible spectrum. Also absorption coefficient, extinction coefficient and the optical energy gap (Eg) was calculated, found that the film have direct energy gap equal to 2.8 eV.